Dalfampridine improves walking speed, walking endurance, and community participation in veterans with multiple sclerosis: a longitudinal cohort study. (May 2014) - Cameron, Michelle H; Fitzpatrick, Mary; Overs, Shannon; Murchison, Charles; Manning, Jane; Whitham, Ruth
Background: In short-term trials, dalfampridine extended release (ER) improves walking in people with multiple sclerosis (MS). The tolerability and effects of dalfampridine-ER in clinical practice have not been reported. Objectives: The objective of this paper is to determine the clinical tolerability and effects of dalfampridine on walking and community participation. Methods: All patients at the Portland VA Medical Center prescribed dalfampridine-ER over one year completed the Timed 25-Foot Walk (T25FW), Multiple Sclerosis Walking Scale-12 (MSWS-12), Two-Minute Timed Walk (2MTW), and Community Integration Questionnaire (CIQ) at baseline and follow-up clinic visits. Ongoing use and measures over one year were analyzed. Results: A total of 39 patients (mean age 56.5 years, mean disease duration 19.5 years, 82% male, 38% relapsing–remitting MS, 62% progressive MS) were prescribed dalfampridine-ER. Twenty-four (62%) continued to take dalfampridine-ER. At initial follow-up, all measures improved significantly from baseline (T25FW: –2.7 s, p = 0.004; 2MTW: 41 feet (ft), p = 0.002; MSWS12: –11, p < 0.001; CIQ: 1.2, p = 0.003). At one year, walking endurance and self-perceived walking were still significantly improved (2MTW: 33 ft, p = 0.03; MSWS-12: 5.9, p = 0.007). Conclusions: Dalfampridine-ER was associated with short-term improvements in walking speed and community participation, and sustained improvements in walking endurance and self-perceived impact of MS on walking for one year. Our study supports the utility of this medication in late MS.